Management of Fieldwork Practice Supervisors (PKL) in Improving Work Discipline Students of SMK Negeri 2 Luwu Utara - Musdalipa Musdalipa; Baso Sulaiman; Muna Hatija (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research examines the management of the Fieldwork Practice Supervisors (PKL) in improving work discipline and the obstacles faced by the Fieldwork Practice Supervisors (PKL) at SMK Negeri 2 Luwu Utara. The type of research used is qualitative research with a descriptive approach. The subjects of this study were the supervisors of the Fieldwork Practice (PKL) program for students of SMK Negeri 2 Luwu Utara, totaling eight people. Data was obtained by conducting observations, interviews, and documentation. The results showed that: 1) The discipline of students at SMK Negeri 2 Luwu Utara who carried out Fieldwork Practices (PKL) was in good condition. 2) Management supervision of Fieldwork Practices (PKL) in improving the work discipline of students of SMK Negeri 2 Luwu Utara who take part in Fieldwork Practices (PKL) is carried out through three stages, namely: a) planning, b) implementation, and c) supervision consisting of direct supervision and indirect supervision; 3) Obstacles faced by supervisors for fieldwork practices (PKL) in improving the work discipline of students of SMK Negeri 2 Luwu Utara who take part in Fieldwork Practices (PKL) include internal factors originating from students, namely the nature and character of students and external factors, namely those originating from outside students such as the environment; and 4) Solutions to increase the work discipline of students at SMK Negeri 2 Luwu Utara who take part in Fieldwork Practices (PKL), namely by setting an example, providing motivation in applying discipline and imposing sanctions for violations committed.